LB1.4 Improved outcomes following resistance-guided treatment of mycoplasma genitalium infection. (8th July 2017) - Read, Tim RH; Fairley, Christopher K; Jensen, Jorgen S; Murray, Gerald; Worthington, Karen; Doyle, Michelle; Chow, Eric P; Chen, Marcus Y; Bradshaw, Catriona S
Abstract : Introduction: Resistance to 1 st (azithromycin) and 2nd line (moxifloxacin) therapy in Mycoplasma genitalium (MG) now exceeds 50% and 15%, respectively, in the Asia-Pacific region. New approaches to achieve high levels of cure and minimise resistance are urgently needed. We evaluated a novel strategy of switching from azithromycin to doxycycline for MG-associated syndromes and using resistance-guided therapy, with sitafloxacin for macrolide-resistant infections. Methods: From July 2016 Melbourne Sexual Health Centre switched from azithromycin to doxycycline 100 mg twice daily 7 days for non-gonococcal urethritis/cervicitis/proctitis. Cases were tested for MG and macrolide-resistance mutations (MRM) by PCR (ResistancePlus MG test, SpeeDx Pty Ltd). After doxycycline, MG-positive cases without MRM received 2.5g azithromycin (1g then 500 mg daily for 3 days) and MRM-positive cases received sitafloxacin 100 mg twice daily for 7 days. Retest for microbiologic cure and standardised assessment of adherence, side-effects and post-diagnosis sexual contact occurred 14–90 days after the second antibiotic. Those reporting condomless sex or sex with an incompletely treated partner were excluded. Results: Of 162 evaluable MG infections (35 women, 42 heterosexual men, 85 homosexual men, median age 29) diagnosed to 9 March 2017, MRM were detected in 116 [71.6% (95%confidence interval (CI) 64.0–78.4). Microbiologic cure occurred in: 44 of 46 infections without MRM, treated with doxycycline then azithromcyin [95.7% (95%CI 85.2–99.5)] and in 107 of 116 infections with MRM treated with doxycycline then sitafloxacin [92.2% (95%CI 85.8–96.4)]. Mean fall in log10 bacterial load (on doxycycline prior to the 2 nd antibiotic, n=17) was 2.9, p<0.01. Sitafloxacin was associated with diarrhoea (8.6%) and tendon/joint pain (6.0%). Five (3.1%) patients missed >20% of doses of any antibiotic. Conclusion: Switching from azithromycin to doxycycline for presumptive treatment of STI syndromes, and use of resistance-guided therapy cured >92% of MG infections in the context of high levels of antimicrobial resistance.